MUSCLE QUALITY, STRENGTH, AND LOWER EXTREMITY PHYSICAL PERFORMANCE IN THE BALTIMORE LONGITUDINAL STUDY OF AGING - CHILES SHAFFER, N. (J Frailty Aging, 2017)
BACKGROUND: Muscle quality is defined as the force generated by each volumetric unit of muscle tissue. No consensus exists on an optimal measure of muscle quality, impeding comparison across studies and implementation in clinical settings. It is unknown whether muscle quality measures that rely on complex and expensive tests, such as isokinetic dynamometry and computerized tomography correlate with lower extremity performance (LEP) any better than measures derived from simpler and less expensive tests, such as grip strength (Grip) and appendicular lean mass (ALM) assessed by DXA. Additionally, whether muscle quality is more strongly associated with LEP than strength has not been fully tested. OBJECTIVES: This study compares the concurrent validity of alternative measures of muscle quality and characterizes their relationship with LEP. We also whether muscle quality correlates more strongly with LEP than strength alone. DESIGN: Cross-sectional analysis. SETTING: Community. PARTICIPANTS: 365 men and 345 women 65 years of age and older in the Baltimore Longitudinal Study of Aging. MEASURES: Thigh cross-sectional area (TCSA), isokinetic and isometric knee extension strength (ID), BMI adjusted ALM (ALMBMI) from DXA, and Grip. Concurrent validity was assessed as the percent variance of different measures of LEP explained by each muscle quality measure. In addition, we compared LEP relationships between each measure of strength and its correspondent value of muscle quality. Confidence intervals for differences in percent variance were calculated by bootstrapping. RESULTS: Grip/ALMBMI explained as much variance as ID/TCSA across all LEP measures in women and most in men. Across all LEP measures, strength explained as much variance of LEP as muscle quality. CONCLUSIONS: Grip/ALMBMI and ID/TCSA measures had similar correlations with LEP. Muscle quality did not outperform strength. Although evaluating muscle quality may be useful to assess age-related mechanisms of change in muscle strength, measures of strength alone may suffice to understand the relationship between muscle and LEP.